Cartridge-Based Nucleic Acid Amplification for Rapid Tuberculosis Diagnosis - Rajni Tanwar; Ramesh Kumar; Amandeep Mor; Dinesh Kumar (International Journal of Pathogens, 2024)
In terms of public health, tuberculosis continues to have a significant impact on people's lives. The process of determining the underlying cause of a sickness or condition in a patient is known as clinical diagnosis. It entails the use of numerous diagnostic methods, including physical examinations, laboratory testing, and imaging procedures for medical purposes. Smear microscopy, which are frequently utilized, have poor sensitivity and lengthy turnaround times, respectively. An innovative, quick, cartridge-based molecular test called the GeneXpert (GX) assay has a well-established use for the quick identification of pulmonary and extrapulmonary Mycobacterium tuberculosis (MTB) infections. This device delivers a report indicating whether the sample tested positive or negative for TB after around two hours. The report offers details on the quantity of TB bacteria found in the sample, which can help determine treatment choices. HIV, hepatitis C, and gonorrhea are just a few of the infectious disorders that the GeneXpert system can identify. It is also used to detect the SARS-COV-2 virus-related illness known as COVID-19.
Keywords: GeneXpert; Infection; diagnosis; mycobacterium tuberculosis; rapid testing technologies